Shivering Hopes: A Qualitative Inquiry into the Experiences of Family Caregivers of Critically Ill Patients Reliant on Health Care Technology - Olaolorunpo Olorunfemi; Chinomso Ugochukwu Nwozichi; Christiana Olarewaju Sowunmi (Florence Nightingale Journal of Nursing)
Aim: The aim of the study was to assess the lived experience of family caregivers of critically ill patients sustained by healthcare technologies in Benin-City, Nigeria.